Shear test as calibration experiment for DEM simulations: a sensitivity study. Issue 3 (3rd May 2016) - Keppler, Istvan; Safranyik, Ferenc; Oldal, Istvan
Abstract : Purpose: – The purpose of this paper is to study the effect of micromechanical parameters on the macromechanical behavior of granular materials using discrete element based model of the standard shear test. Design/methodology/approach: – Discrete element method (DEM) based standard shear test simulations. Findings: – The approximate mathematical functions related to the effects of DEM micromechanical parameters density, Young modulus, Poisson number, frictional angle, bond normal cohesion, bond tangential cohesion, rolling friction and particle shape on the macromechanical parameters of shear failure line (internal friction and cohesion) are determined by modeling large number of standard shear tests. Originality/value: – By knowing these effects of micromechanical parameters to the macromechanical behavior of the simulated particle assembly, the calibration of discrete element models can be significantly accelerated.